THE ONOMATOPOEIA IN ROBERT VENDETTI’S COMIC “THE FLASH” - Abd. Muin; Masykur Rauf; Amrullah Nur Hidayat (UIN Alauddin Makassar, 2016)
AbstractThis research studied about the onomatopoeia in Robert Vendetti’s comic “The Flash”. The aims of this research was to find the kinds of onomatopoeia that are used by the author in The Flash comics and to know the lexical and contextual meanings of those onomatopoeia words in The Flash comic. This research applied descriptive qualitative method where the data were analyzed through Bredin’s theory. The researcher found that there are twenty-nine Onomatopoeia words that applied in The Flash comic and there are some onomatopoeia words that has no lexical meaning and some contextual meaning are similar with the lexical meaning. The researcher concluded that most of onomatopoeia words that applied in The Flash comic is Direct Onomatopoeia and there are only two Associative Onomatopoeia that applied in The Flash comic. The implication of this research is to give more description and comprehending about onomatopoeia. Moreover, it can be a reference for the student of Adab and Humanities faculty who attracted to observe the similar research. AbstrakThe Onomatopoeia in Robert Vendetti’s Comic “The Flash”. Penelitian ini belajar tentang onomatopoeia di Robert Vendetti komik